A Cross Sectional Study on Obesity Among First Year MBBS Students of S. Nijalingappa Medical College, Bagalkot - Pavan S Kalasker; Ashok S Dorle; Selvan Vetri (Medsci Publications, 2015)
Introduction: World health report introduced the term "risk transition" to describe changes in nutrition, alcohol consumption, and other lifestyles that promote development of non-communicable diseases. Sedentary lifestyle and shift to western food habits has led to development of overweight and obesity worldwide. Objective of the study to know the prevalence of obesity and its associated risk factors among first year MBBS (2013 Batch) students. Method: A cross-sectional study was carried out from September to October 2013 among 148 first year MBBS Students of S Nijalingappa Medical College Bagalkot, of 2013 Batch. Results: Prevalence of overweight and obesity was 16.22% & 3.38% respectively. Overall overweight (obesity & overweight) was significantly associated with participation in outdoor games, positive family history of obesity, cardio-vascular disease, type II diabetes mellitus or hypertension and sleep duration of <6hrs and >8hrs per day. Conclusion: The study confirmed the findings of earlier studies carried out in other parts of country. This study reinforces the need to promote healthy life style, food habits and regularity of sleep.